Using Big Data in Criminal Investigations: Between Privacy and Efficiency - Oleksii Tavolzhanskyi; Olena Shumeiko; Oleksandr Burda; Kostiantyn Orobets; Maksym Struchaiev (UIN Sunan Gunung Djati, 2025)
The growing complexity of criminal activity and the exponential expansion of digital data necessitate the integration of Big Data technologies into criminal investigations. This paper examines the legal, technological, and ethical implications of using Big Data in criminal justice systems, with a focus on balancing investigative efficiency and individual privacy rights. The research applies a combination of philosophical and normative legal analysis, along with systemic and historical methods, to assess how these technologies are transforming investigative procedures. Findings highlight the potential of Big Data to enhance investigative accuracy, especially through data mining and predictive analytics, but also underscore serious risks related to data protection and regulatory ambiguity. The paper calls for clearer legal standards, international cooperation, and ethical frameworks to guide the application of Big Data in criminal proceedings. Furthermore, it emphasizes the need for institutional accountability and judicial oversight to prevent misuse, ensure transparency, and uphold the rule of law in an increasingly data-driven legal landscape.